2022
DOI: 10.3389/fmed.2022.894338
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Integrative Analysis of Lung Adenocarcinoma: An in silico Profiling for Precise Medicine

Abstract: Lung adenocarcinoma (LUAD) is one of the most common histological subtypes of lung cancer. The aim of this study was to construct consensus clusters based on multi-omics data and multiple algorithms. In order to identify specific molecular characteristics and facilitate the use of precision medicine on patients we used gene expression, DNA methylation, gene mutations, copy number variation data, and clinical data of LUAD patients for clustering. Consensus clusters were obtained using a consensus ensemble of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In recent years, several studies in LUAD research have employed omics integration to achieve more refined patient stratification. For instance, in a comprehensive study by Ruan et al 51 five different omics data were integrated, including DNA methylation, to identify patient consensus clusters, followed by linking these subtypes to treatment strategies. In another study, 12 researchers explored the utility of DNA methylation data for LUAD patient classification, employing unsupervised bootstrap clustering.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies in LUAD research have employed omics integration to achieve more refined patient stratification. For instance, in a comprehensive study by Ruan et al 51 five different omics data were integrated, including DNA methylation, to identify patient consensus clusters, followed by linking these subtypes to treatment strategies. In another study, 12 researchers explored the utility of DNA methylation data for LUAD patient classification, employing unsupervised bootstrap clustering.…”
Section: Discussionmentioning
confidence: 99%
“…We then validated its diagnostic and prognostic potential on an independent large cohort of CRC patients. Previous studies have demonstrated that multi-omics Frontiers in Genetics frontiersin.org analysis (using whole-genome gene expression profiling, copy number variations (CNVs), proteomics, metabolomics, and others) may lead to reliable biomarkers that are robust in disease classification and may also help identify cancer driver genes that are involved in tumor initiation and progression (Colak et al, 2010;Colak et al, 2013;Ohshima et al, 2017;Liu et al, 2021;Kaya et al, 2022;Ruan et al, 2022). Moreover, integrating omics data with the gene interaction networks has been shown to be a robust methodology that may lead to more reliable and accurate predictive biomarkers for human diseases (Al-Harazi et al, 2016;Ma et al, 2019;Khan et al, 2020;Seifert et al, 2020;Sinkala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since tumorigenesis genes show associations with copy number variations (CNVs) and expression levels, it is possible to increase the diagnostic reliability as well as the predictive potential of prognosis by integrating CNV and gene expression data (Sheng et al, 2011;Miao et al, 2014;Shao et al, 2019;Kaya et al, 2022). Indeed, the previous studies, including our own, reported that the multiomics approach may increase the robustness and reliability of biomarkers associated with complex diseases, including cancer (Miao et al, 2014;Aldosary et al, 2020;Das et al, 2020;Al-Harazi et al, 2021a;Baloni et al, 2021;Kaya et al, 2022;Ruan et al, 2022). Additionally, it has been reported that networkbased approaches have high efficacy in identifying biomarkers for many complex diseases, including several different types of cancer (Wang et al, 2017;Chen et al, 2019;Liu et al, 2019;Uddin et al, 2019;Khan et al, 2020;Al-Harazi et al, 2021b).…”
Section: Introductionmentioning
confidence: 96%
“…The conclusion is CHIAP2 is a potential target for lung adenocarcinoma. 132 Lu's published work in the Journal of Oncology discovered a prognostic biomarker for lung adenocarcinoma, characterized by a ferroptosisrelated long non-coding RNA (lncRNA) signature. Shen's published work in Europe PMC found that WWC2-AS2 is one of the four lncRNAs with reduced expression linked to the prognosis of lung adenocarcinoma in humans.…”
Section: -110mentioning
confidence: 99%